(untitled) (Journal of the College of Basic Education, 2023)
The term self-esteem refers to the extent to which an individual accepts himself, including the positive aspects.negatives and the extent of his assessment of its general characteristics, which include a comprehensive assessment of all its personal aspects.social, educational, and professional, and the lower his self-esteem, the less self-acceptance he is.(Deoux, Wrightsman & Deoux) “Self-esteem includes evaluating the personhimself, whether his assessment of them indicates that they are the same positive or negative